Analysis of bioactive constituents contents and their antioxidant activity in the flowers and leaves of two Lonicera acuminate Wall germplasm. Issue 5 (February 2019) - Ren, Si; He, Shuyue; Deng, Qunxian; Sun, Yaqian; Wang, Lamei
Abstract: "Cuilei 001", "Cuilei 003" two Lonicera acuminate Wall germplasm as test materials, the content of bioactive constituents and antioxidant activity of the flowers and leaves at different periods were discussed. The results showed that the content of polyphenol, flavonoid, and vitamin C (Vc) were the highest in the young leaves of the "Cuilei 001". The scavenging ability of the two germplasms to 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radicals was similar and was highest in the flowers, but in the leaves, the scavenging ability to DPPH free radical gradually decreased with the development of the leaves. The flavonoid content, Vc content, peroxidase (POD) activity, superoxide dismutase (SOD) activity, and DPPH free radical scavenging rate of "Cuilei 001" and "Cuilei 003" were significantly positively correlated, and the polyphenol content and DPPH free radical scavenging rate were significantly negatively correlated.